The essence and necessity of the concept of transition to a green economy - Aminov Fazlitdin Bakhadirovich (THE INNOVATION ECONOMY, 2026)
The article analyzes the theoretical foundations of the concept of a “green” economy, its role in ensuring economic and environmental sustainability, as well as the need for a transition to a green economy in the conditions of Uzbekistan. The author reveals the main factors, principles and socio-economic benefits of the transition to a green economy. The current situation in Uzbekistan in this direction is also illustrated by figures.